Fifth Five Year Plan Draft Annual Plan 1974-75 Planning Department, Uttar Pradesh - Planning Commission (Planning Commission, 1973)
With the advent of the year we into the Five year Plan which marks the 24th year of the planned economic development m the country. the State Plan is an integral part of the Imaginal Plan and, therefore naturally, reflects the priorities and compulsions as the National Plan. Removal of poverty and attain font of economic self-reliance have been defined to be the two brief objectives of the Fifth Five Year Plan. The most important cause of poverty are 11 open unemployment end 11 under employment.
Planning Department, Uttar Pradesh